Exposure to mercury among 9-year-old children and neurobehavioural function. (January 2021) - Lozano, Manuel; Murcia, Mario; Soler-Blasco, Raquel; González, Llúcia; Iriarte, Gorka; Rebagliato, Marisa; Lopez-Espinosa, Maria-Jose; Esplugues, Ana; Ballester, Ferran; Llop, Sabrina
Highlights: Association between postnatal Hg and behaviour was assessed among Spanish children. Hair 9-years old THg associated with worse scores on the CBCL internalizing and total problems scales. Factors such as sex and genetics seem to play a role in this relationship. Boys obtained worse scores in the behaviour scales with increasing THg compared to girls. Effect interactions were also observed for polymorphisms in the GSTP1, BDNF and APOE genes. Abstract: Mercury (Hg) is an environmental neurotoxicant whose main route of exposure in humans is the consumption of seafood. The aim of this study was to explore the relationship between Hg exposure at 9 years old and behaviour assessed at 9 and 11 years old. Study subjects were mother–child pairs participating in the INMA (Environment and Childhood) Project in Valencia (Spain). Total Hg (THg) was measured in hair samples from the children at 9 years old. Behaviour and emotions were assessed at 9 (n = 472) years and 11 (n = 385) years of age using the Child Behaviour Checklist test (CBCL) and the Conners Parents Rating Scale-Revised: Short Form (CPRS-R:S). Furthermore, the attention function was assessed by the Attention Network Test at 11 years old. Socio-demographic, lifestyle and dietary information was collected through questionnaires during pregnancy and childhood. Polymorphism in BDNF, APOE and GSTP1 were genotyped in cord blood DNA. Multivariable negative binomial regression models were built in order to study the association between THg concentrations and the scores obtained by the children at 9 and 11 years old. Effect modification by sex and genetic polymorphisms was assessed. The association between Hg levels and CBCL scores was positive (worse neurobehavioural development) for the CBCL internalizing and total problem scales (Incidence Rate Ratio [95% confidence interval] = 1.07 [1.01, 1.13] and 1.05 [0.99, 1.11], respectively). The association between Hg and the externalizing and total problems CBCL scales and the Attention Deficit Hyperactivity Disorder (ADHD) index of the CPRS-R:S was different according to sex, with boys obtaining worse scores with increasing Hg, compared to girls. Statistically significant interactions were also observed for genetic polymorphisms affecting the association between early exposure to Hg and both CBCL and CPRS-R:S scores. In conclusion, postnatal Hg exposure is associated with poorer neurobehavioural development in 9- and 11-year-old children. Sex and the presence of certain genetic polymorphisms modified this association.